2005
DOI: 10.1002/ajmg.a.30777
|View full text |Cite
|
Sign up to set email alerts
|

Cause of sudden, unexpected death of Prader–Willi syndrome patients with or without growth hormone treatment

Abstract: Patients with Prader-Willi syndrome (PWS) are recognized to have a tendency of sudden, unexpected death (SED), but its exact cause is unknown because of paucity of such case reports. Since growth hormone (GH) treatment was applied to PWS patients worldwide, several cases of death have been reported. However, whether the therapy is directly related to their SED remains unknown, too. We collected 13 deceased PWS patients (Group A, aged 9 months to 34 years) who had never received GH therapy, and seven deceased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 16 publications
3
77
0
Order By: Relevance
“…56 In another study, the rate of death in affected individuals on and off GH did not differ. 57 A study of the natural history of PWS in one region of the United Kingdom found the overall death rate of individuals with PWS to be as high as 3% per year without GH therapy. 58 Thus, the relationship of GH administration to unexpected death remains unclear.…”
Section: Hypogonadismmentioning
confidence: 99%
“…56 In another study, the rate of death in affected individuals on and off GH did not differ. 57 A study of the natural history of PWS in one region of the United Kingdom found the overall death rate of individuals with PWS to be as high as 3% per year without GH therapy. 58 Thus, the relationship of GH administration to unexpected death remains unclear.…”
Section: Hypogonadismmentioning
confidence: 99%
“…PWS is also associated with breathing deficits, rhythm instability, severe sleep apneas, and blunted respiratory responses to hypoxia and hypercapnia that may develop before obesity (Nixon and Brouillette, 2002). PWS breathing deficits are risk factors for an early, unexpected sudden death (Schrander-Stumpel et al, 2004;Nagai et al, 2005); however, the physiological cause is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…First, there was a report of sudden death owing to the use of GH treatment [12]. Although the relationship between the sudden death and GH treatment was completely unclear, Nagai et al [13] subsequently reported that the causes of sudden unexpected death did not differ between PWS patients with or without GH treatment. GH treatment has now become contraindicated for patients who are seriously obese or have a high breathing obstacle.…”
Section: Discussionmentioning
confidence: 99%